Numerical solution of variational problems via parametric quintic spline method - M. Zarebnia; Z. Sarvari (Journal of Hyperstructures)
In this paper, the parametric quintic spline method is used for finding the solution of variational problems associated in engineering and physics. The present approximation reduce the problems to an explicit system of algebraic equations. Some numerical examples are also given to illustrate the accuracy and applicability of the presented method.